Penerapan Metode Six Sigma untuk Meminimalkan Produk Cacat pada UMKM X di Industri Manufaktur Sepatu - Fahmi Arif Fajar; Mumu Komaro; Wiku Larutama (Pusat riset dan Inovasi Nasional, 2025)
Operational efficiency and product quality are crucial for enhancing the competitiveness of MSMEs in the era of globalization and digital transformation. This study explores the application of Six Sigma to reduce product defects at MSME X, a footwear manufacturer in Bandung. Using a quantitative approach with interviews, documentation, and observation, the research applied the DMAIC (Define, Measure, Analyze, Improve, Control) framework to identify and address quality issues. Key defects included joint cracks, under-fill, and press marks. Analysis using Pareto charts and cause-and-effect diagrams revealed root causes such as inadequate operator training, inconsistent raw materials, and irregular machine maintenance. To address these, the company implemented retraining programs, improved standard operating procedures, and adopted digital monitoring systems. As a result, the defect rate was reduced by 40%, and the sigma level improved from 3.9 to 4.45. The study confirms that Six Sigma can significantly enhance both product quality and operational performance. These findings offer valuable insights for other MSMEs aiming to adopt structured quality improvement methods to remain competitive in the global market.